Reconstruction of Soft Tissue Defect with Exposed Spine by Latissimus Dorsi Myocutaneous Flap–reconstructive Challenge and our Experience (Journal of Rangpur Medical College, 2026)
Background: Reconstructive surgeons face challenges when repairing soft tissue defects with exposed spine due to the curved contour and strong skin tension of the back. Implant and metal exposure complicates coverage, and patients are often malnourished and fragile. Objective: The purpose of this study was to share our experience regarding reconstruction of soft tissue defects with exposed spine using Latissimus dorsi (LD) myocutaneous flap. Methods: This was a prospective observational study, conducted in the Burn & Plastic Surgery department of Rangpur medical college hospital, Rangpur over a period of three years July 2019 to June 2022. Here 15 patients with soft tissue defect in posterior midline with exposed spine were reconstructed with Pedicled Latissimus dorsi (LD) flap. Patient demographics, clinical details, reconstructive procedures, outcome, and complications were analyzed. Results: Among 15 patients, 12 were male and 03 were females, with male to female ratio of 4:1. The lowest age was 18 years and the highest age was 66 years. The major cause (80%) was post operative soft tissue defect and in 20 % case it was due to high voltage electric burn. In 8 cases there were exposed implants. The standard myocutaneous flap was harvested in all cases. The donor site was closed primarily in all cases. In 03 cases skin graft was placed over transferred muscle. The outcome of reconstruction was satisfactory in all cases. Four patients had minor complications (managed non operatively), one of the patients had surgical site infection which was controlled according to culture-specific antibiotics, and another two patients had partial dehiscence of donor site wound which healed spontaneously. One patient developed seroma in donor site which resolved in time with local care. Conclusion: Pedicled Latissimus dorsi muscle flap is a straight forward and versatile option for reconstruction of soft tissue defect with exposed spine with minimal donor site morbidity.J Rang Med Col.2026 Mar;11(1): 136-140